V magic mask cover / Wesley Chong Kah Ong, Nur Izzah Abdul Majit and Jemaima Litad Jeremy - Ong, Wesley Chong Kah; Abdul Majit, Nur Izzah; Jeremy, Jemaima Litad (Universiti Teknologi MARA, Perak, 2020)
Nowadays, the pandemics are become more and more serious. Everyone needs hygiene masks to protect ourselves from covid-19. But, can you ensure that the place you keep the masks is really totally clean? V Magic Mask Cover is created efficiently for consumers to keep their mask hygiene. V Magic Mask Cover can be used at any place and at any time. It helps the public to keep their mask hygienic at all times. You just need to put your mask inside the V Magic Mask Cover and that's it. The mask can be protected by the cover of V Magic Mask Cover. Also, it makes us convenient to bring it everywhere. As a conclusion, V Magic Mask Cover is a very good choice for everyone especially during this pandemic period. 'V MAGIC MASK COVER, KEEPS YOUR MASK HYGIENE'.